The role of governance in implementing sustainable global health interventions: review of health system integration for integrated community case management (iCCM) of childhood illnesses - Regina Rabinovich; Koya C Allen; Kate Whitfield; Salim Sadruddin (BMJ Global Health)
Improving health outcomes in countries with the greatest burden of under-5 child mortality requires implementing innovative approaches like integrated community case management (iCCM) to improve coverage and access for hard-to-reach populations. ICCM improves access for hard-to-reach populations by deploying community health workers to manage malaria, diarrhoea and pneumonia. Despite documented impact, challenges remain in programme implementation and sustainability. An analytical review was conducted using evidence from published and grey literature from 2010 to 2019. The goal was to understand the link between governance, policy development and programme sustainability for iCCM. A Governance Analytical Framework revealed thematic challenges and successes for iCCM adaptation to national health systems. Governance in iCCM included the collective problems, actors in coordination and policy-setting, contextual norms and programmatic interactions. Key challenges were country leadership, contextual evidence and information-sharing, dependence on external funding, and disease-specific stovepipes that impede funding and coordination. Countries that tailor and adapt programmes to suit their governance processes and meet their specific needs and capacities are better able to achieve sustainability and impact in iCCM.